Molecular Genetic Analysis of α-Thalassemia in Hamadan Province, West Iran. (2nd September 2020) - Moradi, Keivan; Aznab, Mozaffar; Biglari, Mostafa; Shafieenia, Samaneh; Azimi, Azam; Bijari, Nushin; Alibakhshi, Reza
Abstract: Identifying couples who are carriers of thalassemia-causing mutations, followed by prenatal diagnosis (PND), is undoubtedly an effective way to prevent the birth of children with the disease. Our aim in this study was to report for the first time the spectrum of α-globin gene mutations in the population living in Hamadan Province, West Iran. Multiplex gap-polymerase chain reaction (gap-PCR), amplification refractory mutation system (ARMS)-PCR, and direct DNA sequencing of HBA1 and HBA2 genes were used to identify the α-thalassemia (α-thal)-causing mutations in a cohort of 389 individuals including 328 α-thal carriers and 61 normal subjects. A total of 17 different mutations and 25 different genotypes were detected. The –α 3.7 (rightward) deletion (NG_000006.1: g.34164_37967del3804) was the most frequent mutation, accounting for more than half of all mutations (61.04%). This study revealed that there is a variety of α-thal mutations and α-thal genotypes in Hamadan Province, West Iran. This observation is probably due to the complexity of the Hamadan Province population that is composed of Persians (Fars), Turks, Kurds, and Lurs/Laks. In conclusion, our results demonstrated the spectrum of mutations in α-globin genes in Iran and increased our understanding of their distribution in this country.